Konservatif dan Progresif Spritualisme dalam Novel Bilangan Fu Karya Ayu Utami - Helvira, Helvira; WS, Hasanuddin; Nurizzati, Nurizzati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study were to describe the conservative and progressive spiritualism in novel Bilangan Fu by Ayu Utami. The type of this study was the qualitative study by using descriptive method. The data of this study were the quote of sentences that had the conservative spiritualism behavior and progressive spiritualism that searched through the main intrinsic which were: characteristics, setting, and allure. The resources of data in this study in novel Bilangan Fu by Ayu Utami. The results of this were: (1) the characteristics, setting, and allure in novel Bilangan Fu, (2) the consertive spiritualism behavior in novel Bilangan Fu, and (3) the progressive spiritualism behavior in novel Bilangan Fu.